Regulation of EPCs: The Gateway to Blood Vessel Formation. (22nd September 2014) - Parham, Kate A.; Pitson, Stuart M.; Bonder, Claudine S.
Abstract : Endothelial progenitor cells (EPCs) are primitive endothelial precursors which are known to functionally contribute to the pathogenesis of disease. To date a number of distinct subtypes of these cells have been described, with differing maturation status, cellular phenotype, and function. Although there is much debate on which subtype constitutes the true EPC population, all subtypes have endothelial characteristics and contribute to neovascularisation. Vasculogenesis, the process by which EPCs contribute to blood vessel formation, can be dysregulated in disease with overabundant vasculogenesis in the context of solid tumours, leading to tumour growth and metastasis, and conversely insufficient vasculogenesis can be present in an ischemic environment. Importantly, it is widely known that transcription factors tightly regulate cellular phenotype and function by controlling the expression of particular target genes and in turn regulating specific signalling pathways. This suggests that transcriptional regulators may be potential therapeutic targets to control EPC function. Herein, we discuss the observed EPC subtypes described in the literature and review recent studies describing the role of a number of transcriptional families in the regulation of EPC phenotype and function in normal and pathological conditions.